IMPLEMENTASI PROGRAM PENDIDIKAN KARAKTER DI SMPN 2 LILIRILAU KABUPATEN SOPPENG - Askal Munir; Elpisah Elpisah; Husain AS; Muhammad Rakib (STKIP Pembangunan Indonesia Makassar, 2018)
This study aims to determine the implementation of planning, implementation, and evaluation in the character education program and to find out the supporting and inhibiting factors in the character education program at SMPN 2 Lilirilau Soppeng Regency.This research uses descriptive qualitative research. The research subjects and information sources were the principal, deputy head of the curriculum section, deputy head of the student section, counseling teacher, Islamic Education subject teacher, PKn subject teacher, and social studies subject teacher. The technique of data collection is done by observation, interviews and review of the documents of the SMPN 2 Lilirilau Soppeng Regency. The data analysis technique uses qualitative descriptive analysis. In analyzing the data, steps are taken, namely (1) data reduction, (2) data presentation, and (3) conclusions and verification. The validity test of the data is done by triangulation.The conclusions in this study are, 1) Planning for the implementation of character education programs at SMPN 2 Lilirilau Soppeng Regency is carried out through 3 processes, namely socialization of character education, compiling curriculum, and managing school culture and extracurricular activities; 2) Implementation of the character education program at SMPN 2 Lilirilau Soppeng Regency is carried out in: (a) learning activities, (b) school cultural activities; and (c) extracurricular activities. 3) Evaluation of the implementation of character education programs at SMPN 2 Lilirilau Soppeng Regency, namely supervision, monitoring, evaluation and reporting of implementation. 4) Supporting and inhibiting factors for the implementation of character education programs at SMPN 2 Lilirilau Soppeng Regency, namely supporting factors include (a) conducive situation, (b) programmed activities, (c) supporting infrastructure facilities, (d) Human Resources, leadership, and good teacher attitudes, while inhibiting factors include: (a) lack of communication between the school and parents, (b) awareness of students who are still lacking, and (c) different understanding of school people about character education. Keywords: Implementation, Character Education Program